The correlation between white matter hyperintensity and balance disorder and fall risk: An observational, prospective cohort study - Dong-Chao Shen (KeAi Communications Co., Ltd., 2016)
Objective: The presence of an association between white matter hyperintensity (WMH) and the risk of falls in older people is uncertain, with little supporting prospective evidence available at present. We aimed to determine whether WMH was associated with dysfunctions of balance and gait, and other sensorimotor factors leading to falls, and the independent factors related to falls in older Chinese people. The protective effect of exercise against falls was also addressed. Methods: In a representative sample of hospital-based individuals aged 50 years and older in China, the patients' history of falls, magnetic resonance imaging data, scores on the 9-item Berg Balance Scale (BBS-9) test and timed up-and-go test (TUGT), and sensorimotor measures of computerized dynamic posturography (CDP) were analyzed. Incident falls were recorded prospectively over a 12-month period. Using regression modeling, the association between the risk of falls and baseline WMH was estimated. Results: Only individuals with severe WMH were at an increased risk of falls, and CDP was more sensitive than BBS-9 in detecting WMH-related balance and gait dysfunction. However, WMH was not an independent predictor of falls. Taller height and overweight or obese body habitus were identified as novel protective factors for falls. Female, fall history, and increased TUGT score were identified as independent risk factors for falls in older Chinese people. Conclusion: Although WMH was associated with an increased risk of falls, it was not an independent predictor. Keywords: White matter hyperintensity, Balance disorder, Gait disorder, Fall risk